A pH-Triggered Self-Unpacking Capsule Containing Zwitterionic Hydrogel-Coated MOF Nanoparticles for Efficient Oral Exendin-4 Delivery - Zhou, Yuhao (Advanced materials (Deerfield Beach, Fla.), 2021)
© 2021 Wiley-VCH GmbH.